Method for preparing porous silicon carbide film by sintering core-shell structure powder

By coating aluminum sol on the surface of silicon carbide particles to form a core-shell structure powder, the problem of insufficient alkali resistance caused by silica residue in SiC ceramic membrane is solved, and the alkali resistance and pore size distribution of the membrane are improved, so as to achieve Low temperature preparation of high-performance silicon carbide films.

CN119143506APending Publication Date: 2024-12-17NANJING TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411412844.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The remaining silica in the existing SiC ceramic membrane during the reaction sintering preparation process leads to insufficient alkali resistance and uneven pore size distribution, which affects its mechanical strength and separation efficiency.

Method used

By coating aluminum sol on the surface of silicon carbide particles, a core-shell structure powder is formed, which promotes the reaction between silica and sintering aid during sintering, evenly distributes sintering aids, reduces the sintering temperature and improves the alkali resistance of the silicon carbide film. .

Benefits of technology

The alkali resistance and pore size distribution uniformity of the porous silicon carbide film are improved, and the preparation of silicon carbide film with high strength and high separation accuracy is achieved, reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143506A_ABST
    Figure CN119143506A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a porous silicon carbide film by sintering core-shell structure powder. The surfaces of the silicon carbide particles are coated with a proper amount of aluminum sol, so that the reaction of silicon dioxide and a sintering aid in the sintering process is promoted, and the chemical stability and the separation performance of the porous silicon carbide film are further improved. Compared with a porous silicon carbide film prepared by mechanically mixing and adding a sintering aid, the prepared porous silicon carbide film has the advantages that the pore size distribution is more uniform, and the alkali resistance is remarkably improved. The method for improving the alkali resistance of the porous silicon carbide membrane is simple, can be well suitable for cleaning pollution of the ceramic membrane by using a chemical cleaning reagent in the industry, and has a very good application prospect in the fields of oil-water separation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous ceramic material preparation, and relates to a method for preparing a porous silicon carbide film by sintering core-shell structure powder. Background Art

[0002] SiC membrane is a new type of inorganic membrane material with excellent mechanical strength, chemical stability, thermal shock resistance and hydrophilicity. In recent years, it has received increasing attention from academia and industry. Compared with polymers (such as PVDF) and inorganic materials (such as Al2O3, ZrO2), SiC membrane has higher efficiency in oil-water emulsion separation. However, most commercial SiC ceramic membranes are prepared by high-temperature (>2000 °C) recrystallization process in an inert atmosphere, and their widespread application is hindered by high manufacturing costs. Therefore, reducing sintering energy consumption and preparation costs has become a key issue in the current ceramic membrane field.

[0003] Reaction sintering is an effective way to achieve low-temperature preparation of SiC membranes. The sintering temperature of silicon carbide ceramic membranes can be reduced to 1050~1400 °C by using silicon dioxide formed by surface oxidation of silicon carbide particles as a sintering neck. Materials such as kaolin, quartz sand, and metal oxides such as Al2O3, CaO, Y2O3 and ZrO2 have been commonly used as sintering additives for the preparation of SiC membranes. However, studies have shown that there is unreacted silicon dioxide in the sintering neck of silicon carbide membranes prepared by reaction sintering, which will lead to poor alkali resistance of silicon carbide membranes. The residual silicon dioxide is mainly due to the uneven dispersion of the reaction sintering aid, which cannot fully consume the silicon dioxide formed by oxidation on the surface of silicon carbide. At the same time, the agglomerated aids on the surface of silicon carbide also lead to uneven pore size distribution of the porous ceramic membrane finally prepared.

[0004] In order to reduce or eliminate the residual silicon dioxide in silicon carbide membranes prepared by reaction sintering, researchers at home and abroad have conducted a lot of research. For example, Yang Yi et al. (J. Membr. Sci., 2017, 541, 500-509) changed the sintering atmosphere from air to argon during the heating process to inhibit the surface oxidation of silicon carbide during the heating process, in order to achieve the purpose of silicon dioxide generation to meet the demand for reaction sintering without excess. However, the sintering atmosphere switching method only improves the alkali corrosion resistance of silicon carbide membranes to a certain extent, and the mechanical strength attenuation caused by chemical corrosion is still obvious. Professor Chen Yunfa of the Institute of Process Engineering, Chinese Academy of Sciences and others (Journal of Process Engineering, 2019, 19, 407-412) tried to maximize the consumption of silicon dioxide by regulating the content of reaction aid alumina. The results showed that the content of reaction aid alumina increased the content of mullite phase and reduced the content of quartz phase, but it could not be completely eliminated. It can be seen that both the "source control" and "end consumption" strategies of silicon dioxide cannot eliminate the silicon dioxide residue in the sintering neck of the silicon carbide film prepared by in-situ reaction sintering, and it is difficult to effectively solve the problem of insufficient corrosion resistance.

[0005] Considering that silicon dioxide mainly comes from the surface oxidation of silicon carbide, the sintering aid is evenly coated on the surface of silicon carbide particles, and the core-shell structure powder is used to promote the sintering process, so as to fully consume the silicon dioxide formed by the surface oxidation of silicon carbide. Therefore, the present invention proposes a new method for coating the surface of silicon carbide particles with a sintering aid and sintering the formed core-shell structure powder to prepare a silicon carbide film. Summary of the invention

[0006] The present invention utilizes core-shell structure sintering to prepare porous silicon carbide membranes, thereby improving the performance of silicon carbide membranes to meet the use requirements of different fields. The present invention promotes the reaction of silicon dioxide and sintering aids during the sintering process by coating an appropriate amount of aluminum sol on the surface of silicon carbide particles, thereby improving the alkali resistance of the porous silicon carbide membrane. This method can not only improve the alkali resistance of the porous silicon carbide membrane, but also obtain a silicon carbide membrane with a narrower pore size distribution, thereby realizing the preparation of a high-strength and high-separation-precision silicon carbide membrane.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a porous silicon carbide membrane by sintering a core-shell structure powder, the specific steps are as follows: (1) Weigh silicon carbide powder and aluminum sol respectively, with the weight of silicon carbide powder accounting for 70-100% of the total weight of the two and the weight of aluminum sol accounting for 0-30% of the total weight of the two; (2) Add the above two substances to an anhydrous ethanol solution, adjust to alkaline conditions with ammonia water, stir magnetically for 12 h, then centrifuge and completely dry in an oven at 80-120 °C; (3) adding a certain amount of polyvinyl alcohol solution and water to the silicon carbide powder coated with aluminum sol obtained in step (2), and continuing to mix and grind until the powder is free of lumps; (4) The mixed powder obtained in step (3) is pressed into a sheet or strip-shaped body by a tablet press at a pressure of 8 MPa; (5) Dry the green body at 25 °C for 8 h, and then dry it in an oven at 80-120 °C for 1 h; (6) The dried green body is placed in a muffle furnace for sintering at 1150-1450 °C for 4 h, and finally cooled to room temperature with the furnace. The heating rate is controlled at 1-2 °C / min, and the sintering atmosphere is air.

[0008] Preferably, the aluminum sol is either zirconium sol or silica sol.

[0009] Preferably, the silicon carbide powder is silicon nitride or titanium carbide powder.

[0010] Preferably, in step (2), aqueous ammonia is added to adjust the pH to 7-11.

[0011] Preferably, the mass concentration of the polyvinyl alcohol solution in step (3) is 5-10%, the amount added is 2-10% of the total mass of the silicon carbide powder coated with aluminum sol, and the amount of water added is 1-5% of the total mass of the silicon carbide powder coated with aluminum sol.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares a porous silicon carbide film by coating the surface of silicon carbide powder with aluminum sol, promotes the reaction between silicon dioxide generated by oxidation of silicon carbide and sintering aids during the sintering process, and further improves the alkali resistance of the porous silicon carbide film, providing a new way for the in-situ sintering preparation of high-performance silicon carbide porous ceramics.

[0013] 2. The surface coating method makes the sintering aid evenly distributed, avoiding the agglomeration of the aid during the sintering process, and the pore size distribution of the porous silicon carbide membrane obtained is narrower. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is the energy spectrum of the silicon carbide powder coated with aluminum sol prepared in Example 1.

[0015] Figure 2 This is the pore size distribution diagram of the silicon carbide ceramic membrane prepared in Example 3.

[0016] Figure 3 This is a graph showing the change in flexural strength of the silicon carbide ceramic film prepared in Example 3 with corrosion time.

[0017] Figure 4 These are optical micrographs of the oil-water emulsion in Example 5 before (Feed) and after (Filtrate) filtration through a silicon carbide membrane. DETAILED DESCRIPTION

[0018] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention, but are not used to limit the scope of implementation of the present invention. Example 1

[0019] A method for preparing a porous silicon carbide membrane by sintering a core-shell structure, the specific steps of which are as follows: (1) Weigh aluminum sol and silicon carbide powder with an average particle size of 5 μm, where the aluminum sol accounts for 9% of the total mass of the two and the silicon carbide powder accounts for 91% of the total mass of the two. Add the two into anhydrous ethanol, adjust the ammonia water to pH 8, then perform magnetic stirring and centrifugal separation, and then dry at 80 °C to obtain silicon carbide powder coated with aluminum sol.

[0020] (2) Adding a polyvinyl alcohol (PVA) solution with a mass fraction of 8% to the silicon carbide powder coated with aluminum sol in step (1), the mass of PVA added is 2% of the total mass in step (1), and the mass of water added is 1% of the total mass in step (1). The grinding time is 20 minutes until the powder is free of lumps.

[0021] (3) Weigh 2.5 g of the uniformly mixed powder and press the mixed powder into a tablet (Ø30 mm × 3 mm) or strip (50 mm × 6 mm × 6 mm) shape using a tablet press at a pressure of 8 MPa.

[0022] (4) Dry the ceramic green body at 25 °C for 8 h and then in an oven at 80 °C for 1 h.

[0023] (5) In an air atmosphere, increase the temperature to 1150 °C at a rate of 2 °C / min and keep at that temperature for 4 h. Finally, cool to room temperature in the furnace.

[0024] from Figure 1 From the distribution of elements, we can see that the three figures from left to right are the TEM image of the powder, the distribution of aluminum elements, and the distribution of carbon elements. The distribution of aluminum and carbon elements is the same, and the additives are evenly distributed on the surface of silicon carbide. The fine ceramic three-point bending method and Archimedes drainage method were used to test the bending strength and porosity of the prepared porous silicon carbide membrane. The results showed that the bending strength was 7.7 MPa and the porosity was about 46.4%. Example 2

[0025] A method for preparing a porous silicon carbide membrane by sintering a core-shell structure, the specific steps of which are as follows: (1) Weigh aluminum sol and silicon carbide powder with an average particle size of 5 μm, where the aluminum sol accounts for 9% of the total mass of the two and the silicon carbide powder accounts for 91% of the total mass of the two. Add the two into anhydrous ethanol, adjust the ammonia water to pH 8, then perform magnetic stirring and centrifugal separation, and then dry at 80 °C to obtain silicon carbide powder coated with aluminum sol.

[0026] (2) Adding a polyvinyl alcohol (PVA) solution with a mass fraction of 8% to the silicon carbide powder coated with aluminum sol in step (1), the mass of PVA added is 2% of the total mass in step (1), and the mass of water added is 1% of the total mass in step (1). The grinding time is 20 minutes until the powder is free of lumps.

[0027] (3) Weigh 2.5 g of the uniformly mixed powder and press the mixed powder into a tablet (Ø30 mm × 3 mm) or strip (50 mm × 6 mm × 6 mm) shape using a tablet press at a pressure of 8 MPa.

[0028] (4) Dry the ceramic green body at 25 °C for 8 h and then in an oven at 80 °C for 1 h.

[0029] (5) In an air atmosphere, increase the temperature to 1250 °C at a rate of 2 °C / min and keep at that temperature for 4 h. Finally, cool to room temperature in the furnace.

[0030] The bending strength and porosity of the prepared porous silicon carbide membrane were tested by the fine ceramic three-point bending method and the Archimedean drainage method. The results showed that the bending strength was 11.0 MPa and the porosity was about 45.2%. Example 3

[0031] A method for preparing a porous silicon carbide membrane by sintering a core-shell structure, the specific steps of which are as follows: (1) Weigh aluminum sol and silicon carbide powder with an average particle size of 5 μm, where the aluminum sol accounts for 23% of the total mass of the two and the silicon carbide powder accounts for 77% of the total mass of the two. Add the two into anhydrous ethanol, adjust the ammonia water to pH 8, then perform magnetic stirring and centrifugal separation, and then dry at 80 °C to obtain silicon carbide powder coated with aluminum sol.

[0032] (2) Add 8% by mass of PVA solution to the aluminum sol-coated silicon carbide powder of step (1), wherein the mass of PVA added is 2% of the total mass of step (1), and the mass of water added is 1% of the total mass of step (1). The grinding time is 20 minutes, until the powder is free of lumps.

[0033] (3) Weigh 2.5 g of the uniformly mixed powder and press the mixed powder into tablets (Ø30 mm × 3 mm) and strips (50 mm × 6 mm × 6 mm) using a tablet press at a pressure of 8 MPa.

[0034] (4) Dry the ceramic green body at 25 °C for 8 h and then in an oven at 80 °C for 1 h.

[0035] (5) In an air atmosphere, increase the temperature to 1250 °C at a rate of 2 °C / min and keep at that temperature for 4 h. Finally, cool to room temperature in the furnace.

[0036] The bending strength and porosity of the prepared porous silicon carbide membrane were tested by fine ceramic three-point bending method and Archimedes drainage method. The results showed that the bending strength was 22.7 MPa and the porosity was about 43.9%. The retention rate of 500 ppm water-in-oil emulsion reached 97.7% under the conditions of 1 bar and 0.18 m / s, and the oil content in the filtered permeate was only 11.4 mg / L. Figure 2 It can be seen that the prepared porous silicon carbide membrane has a narrow pore size distribution with an average pore size of 1.07 μm. Figure 3 It can be seen that the bending strength of the prepared porous silicon carbide membrane reaches stability after being corroded for 5 h under 1wt% NaOH and slightly boiling conditions, and it has good alkali resistance. Example 4

[0037] A method for preparing a porous silicon carbide membrane by sintering a core-shell structure, the specific steps of which are as follows: (1) Weigh aluminum sol and silicon carbide powder with an average particle size of 5 μm, where the aluminum sol accounts for 29% of the total mass of the two and the silicon carbide powder accounts for 71% of the total mass of the two. Add the two into anhydrous ethanol, adjust the ammonia water to pH 8, then perform magnetic stirring and centrifugal separation, and then dry at 80 °C to obtain silicon carbide powder coated with aluminum sol.

[0038] (2) Adding a polyvinyl alcohol (PVA) solution with a mass fraction of 8% to the silicon carbide powder coated with aluminum sol in step (1), the mass of PVA added is 2% of the total mass in step (1), and the mass of water added is 1% of the total mass in step (1). The grinding time is 20 minutes until the powder is free of lumps.

[0039] (3) Weigh 2.5 g of the uniformly mixed powder and press the mixed powder into a tablet (Ø30 mm × 3 mm) or strip (50 mm × 6 mm × 6 mm) shape using a tablet press at a pressure of 8 MPa.

[0040] (4) Dry the ceramic green body at 25 °C for 8 h and then in an oven at 80 °C for 1 h.

[0041] (5) In an air atmosphere, increase the temperature to 1250 °C at a rate of 2 °C / min and keep at that temperature for 4 h. Finally, cool to room temperature in the furnace.

[0042] The bending strength and porosity of the prepared porous silicon carbide membrane were tested by the fine ceramic three-point bending method and the Archimedean drainage method. The results showed that the bending strength was 17.6 MPa and the porosity was about 41.2%. Example 5

[0043] A method for preparing a porous silicon carbide membrane by sintering a core-shell structure, the specific steps of which are as follows: (1) Weigh aluminum sol and silicon carbide powder with an average particle size of 5 μm, where the aluminum sol accounts for 29% of the total mass of the two and the silicon carbide powder accounts for 71% of the total mass of the two. Add the two into anhydrous ethanol, adjust the ammonia water to pH 8, then perform magnetic stirring and centrifugal separation, and then dry at 80 °C to obtain silicon carbide powder coated with aluminum sol.

[0044] (2) Adding a polyvinyl alcohol (PVA) solution with a mass fraction of 8% to the silicon carbide powder coated with aluminum sol in step (1), the mass of PVA added is 2% of the total mass in step (1), and the mass of water added is 1% of the total mass in step (1). The grinding time is 20 minutes until the powder is free of lumps.

[0045] (3) Weigh 2.5 g of the uniformly mixed powder and press the mixed powder into a tablet (Ø30 mm × 3 mm) or strip (50 mm × 6 mm × 6 mm) shape using a tablet press at a pressure of 8 MPa.

[0046] (4) Dry the ceramic green body at 25 °C for 8 h and then in an oven at 80 °C for 1 h.

[0047] (5) In an air atmosphere, increase the temperature to 1350 °C at a rate of 2 °C / min and keep at this temperature for 4 h. Finally, cool to room temperature in the furnace.

[0048] The bending strength and porosity of the prepared porous silicon carbide membrane were tested using the fine ceramic three-point bending method and the Archimedean drainage method. The results showed that the bending strength was 19.6 MPa and the porosity was about 40.8%. Figure 4 It can be seen that after filtration by the silicon carbide membrane, the permeate is clear and transparent, and almost no oil droplets are observed, proving that the silicon carbide membrane has excellent oil-water separation performance.

Claims

1. A method for preparing a porous silicon carbide membrane by sintering a core-shell structure powder. It is characterized in that The specific steps are as follows: (1) Weigh silicon carbide powder and aluminum sol respectively, with the weight of silicon carbide powder accounting for 70-100% of the total weight of the two and the weight of aluminum sol accounting for 0-30% of the total weight of the two; (2) Add the above two substances to an anhydrous ethanol solution, adjust to alkaline conditions with ammonia water, stir magnetically for 12 h, then centrifuge and completely dry in an oven at 80-120 °C; (3) adding a certain amount of polyvinyl alcohol solution and water to the silicon carbide powder coated with aluminum sol obtained in step (2), and continuing to mix and grind until the powder is free of lumps; (4) The mixed powder obtained in step (3) is pressed into a sheet or strip-shaped body by a tablet press at a pressure of 8 MPa; (5) Dry the green body at 25 °C for 8 h, and then dry it in an oven at 80-120 °C for 1 h; (6) The dried green body is placed in a muffle furnace for sintering at 1150-1450 °C for 4 h, and finally cooled to room temperature with the furnace. The heating rate is controlled at 1-2 °C / min, and the sintering atmosphere is air.

2. The method for preparing a porous silicon carbide membrane by sintering a core-shell structure powder according to claim 1, It is characterized in that The aluminum sol is either zirconium sol or silica sol.

3. The method for preparing a porous silicon carbide membrane by sintering a core-shell structure powder according to claim 1, It is characterized in that The silicon carbide powder is silicon nitride or titanium carbide powder.

4. The method for preparing a porous silicon carbide membrane by sintering a core-shell structure powder according to claim 1, It is characterized in that In step (2), ammonia water is added to adjust the pH to 7-11.

5. The method for preparing a porous silicon carbide membrane by sintering a core-shell structure powder according to claim 1, It is characterized in that The mass concentration of the polyvinyl alcohol solution in step (3) is 5-10%, the amount added is 2-10% of the total mass of the silicon carbide powder coated with aluminum sol, and the amount of water added is 1-5% of the total mass of the silicon carbide powder coated with aluminum sol.

Citation Information

Patent Citations

  • Method for preparing high-performance aluminum base silicon carbide

    CN108580922A

  • Low temperature high-performance silicon carbide film and preparation method thereof

    CN109761612A

  • Silicon carbide molecular sieve membrane support and application thereof in molecular sieve membrane

    CN113800942A

  • Silicon carbide ceramic as well as preparation method and application thereof

    CN114956828A

  • Method for improving mechanical strength of porous silicon carbide film

    CN115745618A